Seismic analysis for multi-story building horizontally damped above basement level - 611482 Mohammed Ziauddin Patowary; Abdul Kadir Marsono, supervisor; Mohd. Zamri Ramli, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Struktur) - Universiti Teknologi Malaysia, 2017